Modernisation at the expense of nature exploitation: An Ecocritical Analysis of The God of Small Things - Patidar, Ranjana; Sambre, Dr. Manik (SMART MOVES JOURNAL IJELLH, 2019)
The literature is the most effective medium to mirror the contemporary society. Many authors creatively used nature as the setting of their works, and treat nature as an important part of human lives. The strong bond between the nature and society efficaciously caught the attention of the literary critics and environmentalists. Now-a-days Ecology and Ecocriticism became the noteworthy tool for literary researches. Environmental analysis is the need of present time, as people getting aware of environment. Therefore, these days numerous plans and schemes are being launched by the government and other organisations to make people environment conscious. At present protection of environment becomes the issue of much importance as we are facing global crisis. My paper seeks to outline eco-critical investigation to the application and the exploitation of nature in the name of civilisation and advancement in the booker prize winning fiction The God of Small Things authored by Arundhati Roy. Many Indian writers have concentrated their consideration on the significance of eco-balance and environmental equilibrium and promote the sensible co-relation between nature and mankind.